The Benediction of St Patrick!! - (:unkn) unknown (Holland, William, 1801)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Ireland -- History -- Union, 1801; Ireland ? Relations ? Great Britain